Progressive resistance and flexibility exercises versus usual care advice for improving pain and function after distal radius fracture in adults aged 50 years or over: protocol for the WISE randomized superiority trial - David J. Keene; Juul Achten; Ioana Marian; Marloes Franssen; Elizabeth Tutton; Warren Sheehan; Colin Forde; Hannah Crook; Jenny Gould; Richard Grant; Duncan Appelbe; Sarah E. Lamb; et al. (Bone & Joint Open)
Aims: Distal radius fractures are very common injuries; the majority affect females aged 50 years or over. Most patients experience pain and stiffness in their wrist and upper limb weakness, making activities of daily living difficult. The aim of the WISE (Wrist Injury Strengthening Exercise) trial is to assess the effectiveness of a flexibility and resistance exercise programme for the upper limb compared with usual care advice after distal radius fracture. Methods: This is a multicentre, parallel-group, superiority, individually randomized controlled trial. We aim to recruit 588 participants aged 50 years and older with a distal radius fracture treated surgically or non-surgically from at least 15 UK NHS hospitals. Participants will be randomized 1:1 using a web-based service to usual care advice plus a therapist-supervised exercise programme (three one-to-one therapy sessions of tailored advice and prescribed home exercise over 12 weeks) or usual care advice only. The primary outcome is participant-reported wrist-related pain and function six months after randomization, measured by the Patient-Rated Wrist Evaluation. Secondary outcomes at three and six months measure health-related quality of life, pain, physical function, self-efficacy, exercise adherence, grip strength, complications, and resource use. Conclusion: This study will assess whether a therapist-supervised exercise programme is more clinically effective than usual care advice for people aged 50 years and older after distal radius fracture. At the time of submission, the trial is currently completing recruitment; follow-up will be completed in 2025 (ISRCTN registry identifier: ISRCTN78953418). Cite this article: Bone Jt Open 2025;6(7):764–784.